Ten years of Israel's organ transplant law: is it on the right track? - Jeffrey Zaltzman (BMC, 2018)
Abstract The Israeli organ donor law was established in 2008. In the ensuing 10 years there have been some improvements in deceased donation and living donor rates and a reduction in the unethical practice of transplant tourism. There is, however, controversy regarding increased access to transplant for those who have been living donors, who are family members of deceased donors, or who have registered their intent to donate. The issue of routine retrieval versus obtaining consent for organ donation has also been raised. This commentary will address these issue, and propose some steps for improvement of the current Israeli organ donation system.